Balanced Notch-Wnt signaling interplay is required for mouse embryo and fetal development. Issue 4 (April 2021) - Batista, Mariana R; Diniz, Patrícia; Murta, Daniel; Torres, Ana; Lopes-da-Costa, Luís; Silva, Elisabete
Abstract : This study investigated the role of Notch and Wnt cell signaling interplay in the mouse early embryo, and its effects on fetal development. Developmental kinetics was evaluated in embryos in vitro cultured from the 8-16-cell to the hatched blastocyst stage in the presence of signaling inhibitors of Notch (DAPT) and/or Wnt (DKK1). An embryo subset was evaluated for differential cell count and gene transcription of Notch (receptors Notch1 - 4, ligands Dll1, Dll4, Jagged1 - 2, effectors Hes1 - 2 ) and Wnt ( Wnt3a, Lrp6, Gsk3β, C-myc, Tcf4, β-catenin ) components, E-cadherin and pluripotency and differentiation markers ( Sox2, Oct4, Klf4, Cdx2 ), whereas a second subset was evaluated for implantation ability and development to term following transfer into recipients. Notch and Wnt blockades had significant opposing effects on developmental kinetics – Notch blockade retarded while Wnt blockade fastened development. This evidences that Notch and Wnt regulate the pace of embryo kinetics by respectively speeding and braking development. Blockades significantly changed the transcription profile of Sox2, Oct4, Klf4 and Cdx2, and Notch and double blockades significantly changed embryonic cell numbers and cell ratio. The double blockade induced more severe phenotypes than those expected from the cumulative effects of single blockades. Implantation ability was unaffected, but Notch and double blockades significantly decreased fetal development to term. Compared to control embryos, Notch blockade and Wnt blockade embryos originated, respectively, significantly lighter and heavier fetuses. In conclusion, Notch and Wnt signaling interplay in the regulation of the pace of early embryo kinetics, and their actions at this stage have significant carry-over effects on later fetal development to term.